PREFERENSI PERTUMBUHAN BIBIT GEMBILI [Dioscorea esculenta (Lour.) Burkill] ASAL BAHAN TANAM DAN TEKNIK PENANAMAN BERBEDA - Ning Wikan Utami; Peni Lestari; Albert Husein Wawo (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Lesser yam (Dioscorea esculenta (Lour.) Burkill) tubers have two important roles in conventional cultivation, as the food as well as the propagation material. The stem cuttings technique is reported can not produce tubers, while micropropagation is less efficient due to the need of large capital, experts, and specific tools. The other hand, farmers are less interested in cultivating this commodity. It has been reported that mini tuber sett can be used for propagation, but it has not been able to explain the growth preferences in each part of the tuber and its effect on yield. The research aims to provide information about the growth preference of lesser yam seedlings from different planting materials and planting techniques and their effects on yields. The research was carried out in Research Center for Biology, LIPI, Cibinong. The experiment was arranged based on split plots with tubers (apical and basal parts) as the main plot and planting position (vertical and horizontal) as subplots. Each treatment was replicated 3 times, with 5 samples for each replication. The results revealed that the apical part produced better shoots and roots than the basal section. The apical dominance of the lesser yam tuber was very high. It is herefore buds that form in the apical tended to grow faster. This section also produced tuber with a better character. With this information, farmers recommended to use planting materials from the apical part of the tuber with horizontal planting position.